EVALUASI LAPORAN KINERJA INSTITUSI PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) PROVINSI SULAWESI UTARA - Simanjuntak, Lucyana Aprillya; Manossoh, Hendrik; Rondonuwu, Sintje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
The performance report of government agencies performance is a form of accountability in presenting, reporting and disclosing the mission of the agency in the form of activities and activities that are the responsibility of the stakeholders who have the right and authority to request such accountability. Performance Reports presented in accordance with applicable regulations can be utilized to make a decision and steps to be taken in the future in improving agency performance. This study aims to determine the performance report of BAPPEDA has been presented in accordance with the regulations and assess the work achievements of BAPPEDA. The analytical method used is descriptive qualitative. The results of this study indicate that the BAPPEDA performance report is in accordance with the guidelines of the State administration agency (LAN) and the BAPPEDA performance achievements are in good class so that the BAPPEDA performance report can be used for decision making.